Critérios de escolha da semente de soja pelos agricultores da região de Rondonópolis - MT - Miyata, Patrícia Akiko (2012)
The present work had the objective to conduct a survey of the factors that the producer of soybean grain considers the choice of seed lots, and companies producing cultivars of soybean seeds. For such knowledge is made use of a questionnaire with nine open and two closed questions applied via telephone, farmers in the region of Rondonopolis, Black Stone and Itiquira, totaling 25 interviews in which the majority of respondents were Rondonópolis The completion of the interviews occurred between March and April 2012. After tabulating the data obtained from the survey can be concluded that the main factor that producers of soybeans take into consideration when choosing to use the seed physiological quality is the same and that cultivars should provide resistance to nematodes and diseases, and the early cycle also be considerable.